STRATEGIC MARKETING AND THE SYSTEM OF CREATING CUSTOMER VALUE AT THE TIME OF TRANSITION TO THE KNOWLEDGE ECONOMY - I. Semenov (Вестник университета)
The article deals with the organization’s strategic marketing (SM) influence on the system of creating customer value (CCV) at the time of transition to the knowledge economy. At first the author recognizes limitations of the traditional approach to the SM and proposes the typology of market behavior strategies of the organization. Then the comparative analysis of the system of CCV differences between long-linked and network market models is used for the explanation of the new role of the SM. In conclusion the article suggests discussion questions and future investigations in this field.